P477 Rectal bleeding and stool frequency improvement with tofacitinib retreatment in patients with Ulcerative Colitis after treatment interruption: Results from OCTAVE Open. (21st January 2022) - Allegretti, J R; Gecse, K B; Chiorean, M V; Argollo, M; Guo, X; Lawendy, N; Su, C; Mundayat, R; Paulissen, J; Salese, L; Irving, P M
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). Patients may require retreatment following treatment interruption for reasons such as adverse events or pregnancy. 1 In the tofacitinib UC clinical programme, patients who responded to tofacitinib 10 mg BID during induction, and experienced treatment failure whilst receiving placebo during maintenance (OCTAVE Sustain) and subsequently received tofacitinib 10 mg BID in the open-label, long-term extension (OLE) study (OCTAVE Open; NCT01470612), comprised the retreatment subpopulation. The efficacy and safety of tofacitinib in the retreatment subpopulation have previously been reported. 1 Here, we evaluated patient-reported outcomes to assess rectal bleeding and stool frequency improvement in the retreatment subpopulation in OCTAVE Open. Methods: The following efficacy endpoints based on the Mayo subscores were analysed in the overall retreatment subpopulation and by prior tumour necrosis factor inhibitor (TNFi) failure status: rectal bleeding improvement (≥1 point decrease in rectal bleeding subscore [RBS] from OLE study baseline), and stool frequency improvement (≥1 point decrease in stool frequency subscore [SFS] from OLE study baseline), up to Month (M)6 in the OLE study (full analysis set, non-responder imputation). Changes from baseline in partial Mayo score (PMS), RBS and SFS at M1, by M2 clinical response status, were also analysed (as observed). Results: In OCTAVE Open, 101 patients were included in the retreatment subpopulation, of which 46 (45.5%) had prior TNFi failure. Overall, at M1 and M6 of OCTAVE Open, 83.2% and 76.2% of patients had rectal bleeding improvement, respectively (Figure 1). Corresponding values for stool frequency improvement were 70.3% and 75.2%. At most time points, rates of rectal bleeding and stool frequency improvements were similar in patients with and without prior TNFi failure. Mean decrease from baseline in PMS, RBS and SFS at M1 was similar in patients with and without a clinical response at M2 (Figure 2). Conclusion: In this post hoc analysis, in patients with UC who had loss of response after 8–52 weeks of treatment interruption, retreatment with tofacitinib 10 mg BID resulted in rectal bleeding and stool frequency improvement in the majority of patients by M1, which was maintained to M6, regardless of prior TNFi failure status. Reference: 1. Panés J et al. J Crohns Colitis 2021. Epub ahead of print.